Wage subsidies and international trade: When does policy coordination pay? - Sebastian Braun; Christian Spielmann (Kiel Institute for the World Economy (IfW), 2012)
National labour market institutions interact across national boundaries when product markets are global. Labour market policies can thus entail spill-overs, which suggests that there are benefits from international policy coordination. This paper studies the effects of wage subsidies in an international duopoly model with unionised labour markets. The authors document both positive and negative spill-over effects and discuss the benefits and costs from international policy coordination both for the case of symmetric and asymmetric labour market institutions. The results suggest that institutional differences could sign responsible for the slow speed at which labour market policy coordination has progressed so far.
Keywords: F16; F42; J38; H87; 330; wage subsidies; policy spill-overs; international policy coordination; unionised labour markets; trade; asymmetric labour market institutions; Lohnsubvention; Außenwirtschaft; Spillover-Effekt; Duopol; International; Gewerkschaftsmitgliedschaft; Arbeitsmarktpolitik; Internationale wirtschaftspolitische Koordination; Theorie